PENGATURAN WARISAN LOMPAT TANGAN DALAM SISTEM HUKUM PERDATA - Dilla Ayuna Letri; Wirna Rosmely (LPPM Universitas Ekasakti, 2022)
Abstract: Wills are one of the deeds that have long been known before Islam. A will is the gift of an object from the heir to another person or institution that will take effect after the heir dies. The implementation of wills is not only regulated in Islamic law and KHI, Western law that applies in Indonesia as contained in the Civil Code also regulates wills. Inheritance law in Indonesia generally regulates the transfer of wealth/inherited property which is commonly called boedel in relation to the Saisine principle. This happens between the heir as the owner of the property and his heirs. However, it can also happen with a will, an heir transfers/gives a part of the property that has been free from the obligation to give it according to Article 913 of the Civil Code concerning the absolute share to parties who in inheritance law are called parties who expect inheritance by jumping hands/fidei commis. Abstrak: Wasiat merupakan salah satu perbuatan yang sudah lama dikenal sebelum Islam. Wasiat adalah pemberian suatu benda dari pewaris kepada orang lain atau lembaga yang akan berlaku setelah pewaris meninggal dunia. Pelaksanaan wasiat tidak hanya diatur dalam hukum Islam dan KHI, hukum Barat yang berlaku di Indonesia yang tertuang dalam Kitab Undang- Undang Hukum Perdata juga mengatur tentang wasiat. Hukum waris di Indonesia pada umumnya mengatur mengenai perpindahan kekayaan/harta warisan yang biasa disebut boedel dalam kaitannya dengan asas Saisine. Hal yang demikian terjadi antara pewaris selaku pemilik harta dengan para ahli warisnya. Namun demikian dapat terjadi pula dengan suatu wasiat, seorang pewaris memindahkan/memberikan bagian harta yang telah bebas dari kewajiban untuk diberikan menurut Pasal 913 KUHPerdata tentang bagian mutlak kepada para pihak yang didalam hukum waris disebut pihak yang mengharapkan dengan pewarisan secara lompat tangan/fidei commis.